2014
DOI: 10.1186/1476-511x-13-167
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in Ampd2 is associated with nephrotic syndrome and hypercholesterolemia in mice

Abstract: BackgroundPreviously, we identified three loci affecting HDL-cholesterol levels in a screen for ENU-induced mutations in mice and discovered two mutated genes. We sought to identify the third mutated gene and further characterize the mouse phenotype.MethodsWe engaged, DNA sequencing, gene expression profiling, western blotting, lipoprotein characterization, metabolomics assessment, histology and electron microscopy in mouse tissues.ResultsWe identify the third gene as Ampd2, a liver isoform of AMP Deaminase (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…AMP deaminase (Ampd) is the rate-limiting enzyme in the catabolism of AMP to uric acid and is a component of the purine nucleotide cycle, which is responsible for the deamination of AMP to inosine monophosphate ( 61 ). Helmering et al ( 61 ) reported that a mutation in the Ampd2 gene (a liver isoform of Ampd ) leads to nephrotic syndrome and hypercholesterolemia in Ampd2 knockout (KO) mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMP deaminase (Ampd) is the rate-limiting enzyme in the catabolism of AMP to uric acid and is a component of the purine nucleotide cycle, which is responsible for the deamination of AMP to inosine monophosphate ( 61 ). Helmering et al ( 61 ) reported that a mutation in the Ampd2 gene (a liver isoform of Ampd ) leads to nephrotic syndrome and hypercholesterolemia in Ampd2 knockout (KO) mice.…”
Section: Discussionmentioning
confidence: 99%
“…AMP deaminase (Ampd) is the rate-limiting enzyme in the catabolism of AMP to uric acid and is a component of the purine nucleotide cycle, which is responsible for the deamination of AMP to inosine monophosphate ( 61 ). Helmering et al ( 61 ) reported that a mutation in the Ampd2 gene (a liver isoform of Ampd ) leads to nephrotic syndrome and hypercholesterolemia in Ampd2 knockout (KO) mice. It was additionally observed that the Ampd2 KO mice had minimal alterations in the kidneys, minimal to moderate thickening of the GBM, an increase in the cellularity of the mesangial matrix and an increase in inflammatory cells in the glomeruli.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 6 Recently, AMPD2 mutant mice and Ampd2−/− mice have been associated with nephrotic syndrome and proteinuria in the absence of any brain abnormality. 7 A neurodegenerative phenotype has been observed when both Ampd2 and Ampd3 are knocked out, suggesting a functional redundancy among AMP deaminase homologs. However, it remains to be elucidated whether humans carrying AMPD2 mutations may have renal involvement.…”
Section: Discussionmentioning
confidence: 99%
“…AMPD2 is an important enzyme involved in adenosine monophosphate metabolism and plays an important biological function in adenylate metabolism in smooth muscle tissue[ 7 ]. In previous studies, it was shown that AMPD2 affected the nephrotic syndrome and hypercholesterolemia[ 8 ]. In addition, it has been demonstrated that AMPD2 dramatically affected physiological and pathological processes[ 9 ].…”
Section: Introductionmentioning
confidence: 99%